Nonlocal degenerate reaction-diffusion equations with general nonlinear diffusion term - Sikiru Adigun Sanni (Electronic Journal of Differential Equations, 2014)
We study a class of second-order nonlocal degenerate semilinear reaction-diffusion equations with general nonlinear diffusion term. Under a set of conditions on the general nonlinear diffusivity and nonlinear nonlocal source term, we prove global existence and uniqueness results in a subset of a Sobolev space. Furthermore, we prove nonexistence of smooth solution or blow-up of solution under some other set of conditions. Lastly, we give illustrative examples for which our results apply.